Effect of improved land and water management strategies on crop productivity and soil fertility in wastewater irrigated eggplant (Solanum melongena) - G, ROSIN K; KUMAR, SARVENDRA; PATEL, N; LAL, K; KAUR, R; SHARMA, V K (The Indian Journal of Agricultural Sciences, 2020)
Wastewater irrigation with efficient land and water management strategies improve the marketable yield as well as reduce the pollutant threat posed by the irrigation. A field experiment was conducted for two years (2014- 2016) at ICAR- IARI farm, New Delhi to study the effect of municipal wastewater irrigation along with two land configurations (ridge and furrow and basin) and two methods of irrigation (drip and flood) on the yield of eggplant (Solanum melongena cv. Supriya) and soil health. Wastewater irrigated eggplants resulted significantly higher yield (37.1 t/ha), fruit weight (325 g) and fruit diameter (10.02 cm) in the tune of 38, 26 and 7% higher respectively over groundwater irrigated plot. Among irrigation methods, drip irrigation increased yield, fruit weight and fruit diameter of eggplant by 10, 9 and 1% higher over flood irrigation. Significantly higher fruit weight (294 g) of eggplant was recorded with the flat bed system compared to a raised bed system (288 g) and higher yield (4%) was also recorded under a flat bed system over a raised bed system. Wastewater irrigated plots recorded higher plant height, number of branches per plant as compared to groundwater irrigated plants at 120 and 180 days after transplanting. Application of wastewater significantly enhanced available N and P content and DTPA-Pb and Fe in the soil as compared to groundwater irrigated soil. Flood irrigation led to the accumulation of DTPA-Pb and Ni in soil, compared to drip irrigation. Significantly higher dehydrogenase activity, fluorescein diacetate activity and soil microbial biomass carbon were noticed in wastewater irrigated soil as compared to groundwater plots at upper depth (0-5cm). The findings of the present investigation illustrate that wastewater applied through drip irrigation resulted in yield increment as well as reduced metal concentrations in soil.